Delivering a sustainable trauma management training programme tailored for low-resource settings in East, Central and Southern African countries using a cascading course model. Issue 5 (May 2016) - Peter, N.A.; Pandit, H.; Le, G.; Nduhiu, M.; Moro, E.; Lavy, C.
Abstract: Background: Injuries cause five million deaths and 279 Disability Adjusted Life Years (DALYS) each year worldwide. The COSECSA Oxford Orthopaedic Link (COOL) is a multi-country partnership programme that has delivered training in trauma management to nine sub-Saharan countries across a wide-cadre of health-workers using a model of "primary" courses delivered by UK instructors, followed by "cascading" courses led by local faculty. This study examines the impact on knowledge and clinical confidence among health-workers, and compares the performance of "cascading" and "primary" courses delivered in low-resource settings. Methods: Data was collated from 1030 candidates (119 Clinical Officers, 540 Doctors, 260 Nurses and 111 Medical Students) trained over 28 courses (9 "primary" and 19 "cascading" courses) in nine sub-Saharan countries between 2012 and 2013. Knowledge and clinical confidence of candidates were assessed using pre- and post-course MCQs and confidence matrix rating of clinical scenarios. Changes were measured in relation to co-variants of gender, job roles and primary versus cascading courses. Multivariate regression modelling and cost analysis was performed to examine the impact of primary versus cascading courses on candidates' performance. Findings: There was a significant improvement in knowledge (58% to 77%, p < 0.05) and clinical confidence (68% to 90%, p < 0.05) post-course. "Non-doctors" demonstrated a greater improvement in knowledge (22%) and confidence (24%) following the course ( p < 0.05). The degree of improvement of MCQ scores differed significantly, with the cascading courses (21%) outperforming primary courses (15%) ( p < 0.002). This is further supported by multivariate regression modelling where cascading courses are a strong predictor for improvement in MCQ scores (Coef = 4.83, p < 0.05). Interpretation: Trauma management training of health-workers plays a pivotal role in tackling the ever-growing trauma burden in Africa. Our study suggests cascading PTC courses may be an effective model in delivering trauma training in low-resource settings, however further studies are required to determine its efficacy in improving clinical competence and retention of knowledge and skills in the long term.